System Dynamics Model for Reducing Unemployment Rate of Vocational High School Graduate in Indonesia - Assalam, Awla Fajri; Sunitiyoso, Yos (CV. Publikasi Indonesia, 2025)
Sekolah Menengah Kejuruan (SMK) serves as Indonesia's vocational high school system designed to produce work-ready graduates. However, SMK graduates consistently maintain the highest open unemployment rate among all education levels in Indonesia at 9.42% in 2024, significantly higher than Thailand's 0.59% for vocational graduates. This study utilized system dynamics methodology to analyze factors contributing to SMK graduate unemployment and simulate policy interventions to reduce unemployment rates by 2045. Through interviews with 11 stakeholders, literature review, and observations, 34 variables were identified in a Causal Loop Diagram and converted into a Stock Flow Diagram with 54 variables. Twenty-two scenarios were developed across four groups: GDP growth analysis, education budget allocation, budget distribution analysis, and SMK budget composition. Results indicate that maintaining GDP growth above 4.89% or allocating minimum 8.544% of GDP to education budget can eliminate SMK graduate unemployment by 2045. The most effective intervention is increasing student certification budget allocation, which can achieve zero unemployment by 2040. The study recommends implementing